Carboplatin with intravenous and subsequent oral administration of vinorelbine in resected non-small-cell-lung cancer in real-world set-up. - Vítězslav Kolek; Ivona Grygárková; Leona Koubková; Jana Skřičková; Jiřina Švecová; Dimka Sixtová; Jiří Bartoš; Aleš Tichopád (PLoS ONE, 2017)
Adjuvant cisplatin-based chemotherapy is recommended for routine use in patients with Stage IIA, IIB or IIIA non-small cell lung cancer (NSCLC) after complete resection. Results obtained for Stage IB were not conclusive. While vinorelbine plus cisplatin is the preferred choice after resection, combining vinorelbine with carboplatin promises improved compliance and delivery of drugs due to lower toxicity. We evaluated the impact of this option on treatment compliance and survival under real-world conditions.A prospective, single-arm, multicenter, non-interventional study evaluated the tolerability, dose intensity and survival resulting from adjuvant use of intravenous carboplatin (AUC 5 on day 1) with vinorelbine administered both intravenously (25 mg/m2 on day 1) and orally (60 mg/m2 on day 8) within four cycles of 21 days each. A total of 74 patients with a median age of 64 years were observed.The mean number of accomplished cycles was 3.78, and 62 patients (83.7%) completed all four planned cycles. Relative dose intensity for carboplatin was 88.9%, for intravenous vinorelbine 93.1%, and for oral vinorelbine 83.2%. Median follow-up was 4.73 years. Median disease-specific survival (DSS) was 7.63 years, median overall survival (OS) was 5.90 years, median disease-free survival (DFS0) was 4.43 years, and five-year survival was 56.2%. TNM stage of disease significantly affected DSS and OS. Favorable survival was observed in females, nonsmokers, patients aged over 65 years, patient with prior lobectomy, patients with tumor of squamous histology, and those who finished the planned therapy, but the differences were non-significant.Adjuvant carboplatin with vinorelbine switched from intravenous to oral administration was shown to be a favorable regimen with regard to tolerability and safety. Compliance to therapy was high, and survival parameters were promising, showing that applied regimen can be another potential option for adjuvant chemotherapy in patients with NSCLC.